Strengthening the Multi-Party Presidential Government in Indonesia - Hamudy, Moh. Ilham A.; Rifki, M. Saidi (Jurnal Politik Indonesia: Indonesian Political Science Review, 2019)
The Multi-Party Presidential Government in Indonesia has reached a critical point. The 2.5 percent parliamentary threshold rule in the 2009 Election was incapable to address the issue. The parliamentary threshold was raised to 3.5 percent in 2014, in the hope to reduce the number of party joining the election, but it failed to do so. There were 9 national parties participating in the 2009 election, and it will be increased to 16 in the 2019 election. Theoretically, the combination of multi-party parliament in a Presidential Government is rather strange. It is not surprising that the "conflict" between the president and parliament often occurs. There suppose to be a coalition supporting the government in parliament, but the coalition is not a firm one. The coalition did not have a significant influence in strengthening the presidential government. Therefore, this study intends to provide a complete picture of multi-party system practices while trying to provide solutions for strengthening the presidential government in Indonesia. To achieve this goal, this study uses the literature study method in collecting relevant information, using a qualitative approach. This approach is considered appropriate because multi-party phenomena and presidential systems are multidimensional. In contrast to previous research which was limited to the description and problems of multiparty systems, this research besides describing the system of government also provided moderate solutions that were considered to be in accordance with the Indonesian context. This study assumes that strengthening presidential systems can be done if the political parties are more modest. In addition, parliamentary support for the president must be optimized. The results of the study concluded that the strengthening of presidential systems must be carried out through the purification of the government system contained in the constitution, forming and strengthening the ranks of government coalitions in parliament, and carrying out a number of institutional engineering through various forms. These three things must be wrapped in a constitutional frame (amendments to the 1945 Constitution) and regulations (revisions to laws and government regulations). The amendments and revisions can be done through three corridors, namely the intra-parliamentary movement, the extra-parliamentary movement, and the referendum.